Primary Thyroid Diffuse Large B-Cell Lymphoma: Diagnostic and Therapeutic Assessment Using 18F-FDG PET-CT (Bangladesh Journal of Nuclear Medicine, 2026)
Background: Primary thyroid lymphoma is an uncommon malignancy estimated to have an annual incidence of two cases per million population. Diffuse large B-cell lymphoma (DLBCL) is the most frequent histological subtype of primary thyroid lymphoma associated with Hashimoto’s thyroiditis and is considered a curable disease when diagnosed and treated early. Precise diagnosis and staging are crucial, and 18F-FDG PET-CT plays a vital role in both initial assessment and post-therapy response evaluation. Case report: A 50-year-old woman diagnosed with non-Hodgkin lymphoma (NHL) involving the thyroid was referred to the PET-CT division to evaluate the extent of disease. Initially the patient presented with a neck swelling for five months. Neck ultrasound reported a nodular mass of the left lobe of the thyroid gland. Immunohistochemistry confirmed the germinal center type of DLBCL. Baseline PET-CT scan revealed a large lobulated hypermetabolic soft tissue mass involving the left lobe of the thyroid gland with a high SUVmax on 18F-FDG PET-CT. The mass demonstrated extensive local invasion, including retrosternal extension with involvement of the epiglottis, vocal cords, and proximal trachea and erosion of the thyroid & cricoid cartilage. The right lobe of the thyroid gland was mildly enlarged with diffuse FDG uptake. After four cycles of systemic therapy, a follow-up PET-CT scan showed complete morpho-metabolic regression of the thyroid mass, indicating an excellent therapeutic response. Residual diffuse FDG uptake in the right lobe of the thyroid existed and was most likely a sequel of thyroiditis. Conclusion: Reported case reflects the utility of 18F-FDG PET-CT in initial staging and post therapy response assessment of thyroid lymphoma. PET-CT played a pivotal role in detecting the extent of the disease and guiding therapeutic response.Bangladesh J. Nuclear Med. 29(1): 82-87, 2026